2013
DOI: 10.3109/10520295.2013.855323
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase activity-independent function of telomerase reverse transcriptase is involved in acrylamide-induced neuron damage

Abstract: Polyacrylamide is used widely in industry, and its decomposition product, acrylamide (ACR), readily finds its way into commonly consumed cosmetics and baked and fried foods. ACR exerts potent neurotoxic effects in human and animal models. Telomerase reverse transcriptase (TERT), the catalytic subunit of telomerase, traditionally has been considered to play an important role in maintaining telomere length. Emerging evidence has shown, however, that TERT plays an important role in neuroprotection by inhibiting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It has been observed that AM imparts potential genetic, neuro, and reproductive toxicity to humans . AM has a wide range of applications in various industries such as food packaging, paper, and textile and is also used in the separation of proteins. Deep-fried foods (≥120 °C) contain AM as a result of the Maillard reaction between the reducing sugar and amino acid present in food during food processing/cooking. It has been found that AM is predominantly formed by two pathways, i.e., Strecker synthesis (Schiff base as intermediate) and acrolein (decarboxylation of organic acids). , It has been estimated that exposure humans to AM through food and modern industrialization has reached a range of 0.2–1.9 μg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that AM imparts potential genetic, neuro, and reproductive toxicity to humans . AM has a wide range of applications in various industries such as food packaging, paper, and textile and is also used in the separation of proteins. Deep-fried foods (≥120 °C) contain AM as a result of the Maillard reaction between the reducing sugar and amino acid present in food during food processing/cooking. It has been found that AM is predominantly formed by two pathways, i.e., Strecker synthesis (Schiff base as intermediate) and acrolein (decarboxylation of organic acids). , It has been estimated that exposure humans to AM through food and modern industrialization has reached a range of 0.2–1.9 μg/kg.…”
Section: Introductionmentioning
confidence: 99%
“…There are other studies which do not specify IC 50 value after acrylamide treatment, but interval of IC 50 value can be inferred from their data. In this manner, IC 50 of acrylamide-treated rat cortical neurons 14 and V79 cells 15 are extrapolated to be 10 and 4–5 mM, respectively. Rat cortical neurons are more resistant to acrylamide, while V79 cells are as sensitive as A549 cells, IC 50 of both are close.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that ACR exposure resulted in significantly increased ROS production in neuron-associated cell lines (Albalawi et al, 2018;Pan et al, 2015) and in rat cortical neurons (Zhang et al, 2014). We investigated whether ACR exposure can increase ROS production in zebrafish embryos.…”
Section: Ca Treatment Reduced Acr-induced Reactive Oxygen Species (Ros) Production In Zebrafish Embryosmentioning
confidence: 93%